(untitled) (Research, Society and Development, 2021)
Objective: To identify if there is difficulty in diagnosing the pathology due to the varied clinical manifestations and to define if there is a more prevalent cause. Method: The study is an Integrative Literature Review, in which articles were selected from the databases: SciELO and MEDLINE, using as inclusion criteria articles in Portuguese, English and French, published between 1922-2012; addressing the etiopathogenic bias of pellagra; and with methodological delimitation. The descriptors used were: “pellagra”, “niacin” and “clinical manifestations”. The final sample consisted of 6 articles. Results: It was observed that a high percentage of patients present the “Pelagra Sine Pelagra”, that is, without the manifestation of the dermatological lesions characteristic of the pellagra, thus observing only the gastrointestinal and/or neurological disorders, making diagnosis of the pathology difficult. About the prevalent cause, alcoholism is the main risk factor for the onset of the disease. Conclusion: It is understood that the most reported profile was that of oligosymptomatic individuals, especially patients who present “Pelagra Sine Pelagra”. The disease begins with disorders of digestive organs, followed by the appearance of skin lesions, and, finally, nerve alterations. As a result of this sluggish presentation and the fact that it is not always possible to identify the classic triad in patients, there is an obstacle in the diagnosis, both early and in the long term. In addition, some risk factors for pathology have been identified, such as alcoholism, seasonal factors, solar radiation and malnutrition, with alcoholism being the main cause of pellagra nowadays.